Workshop WORKSHOP IMPLEMENTASI PENDIDIKAN KARAKTER MELALUI KEGIATAN MEMBUAT MONTASE DI MTs BUSTANUL ULUM MINGGIRSARI KAB. BLITAR - Latifa, Latifatul Jannah; Ragil, Ragil Tri Oktaviani; Umi, Umi Nahdiyah; Cindy, Cindya Alf (CV. Aksara Global Akademia, 2024)
Some signs that there is currently a moral crisis are increasing promiscuity, rampant corruption, juvenile delinquency, increasing crime, sexual harassment, rampant pornography, drug abuse and many others. These problems require participation from various parties to work together to improve the character of the nation's children, especially teachers and parents. The method of this activity is to use the dissemination method with a workshop. With this method, the resource person will present material about character education and montage work to VII grade students of MTs Bustanul Ulum Minggirsari. This activity was attended by presenters in this case Lecturers and students of UNU Blitar class E21 Minggirsari class. The event was opened by singing the Indonesia Raya song, as well as opening prayers by student representatives, dissemination activities and the last workshop was kneeling and making montages. With this montage workshop, MTs Bustanul Ulum students can hone their skills in making Montage art, and can also develop a cooperative attitude as capital to strengthen character education and keep students away from attitudes that are not in accordance with character education.